Procedures and operating instructions for diagnosisin vascular anomalies and pathology - Moneghini, L.; Mihm, M.C.; Fulcheri, E. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2019)
In the last 30 years a revolution has occurred in the diagnosis and management of vascular anomalies. The great changes began with Mulliken and Glowacki separation of hemangiomas and vascular anomalies. Their work has now morphed into the ISSVA classification. Subsequently the discovery of the significance of the presence of GLUT-1 in the diagnosis of the hemangiomas of infancy gave us a new marker in our quest for accurate classification. Now genetic breakthroughs have led us into a “Star Wars” like environment in the experimental laboratory. During all these events the critical role of the pathologist has become more evident. Understanding the histopathology of anomalies has greatly aided in our approach to therapies. Moreover, genetic findings do not have full significance without the morphologic framework